Size Perception of a Sport Target as a Function of Practice Success Conditions - Bianchi, Krystina; Brillinger, Molly; Patterson, Jae Todd (Frontiers in Psychology, 2022)
Superior motor task success has been correlated with participants’ self-reports of a larger-than-actual size of a sport-related target. In the present study, we examined whether a putting practice condition with greater success would differentially impact participants’ self-reported perceptions of the size of the putting hole during acquisition and retention. We randomly assigned participants to one of three different practice conditions (success-early, success-late, and self-controlled success) and had them self-report their perceived size of the putting hole upon completion of each required putting distance (25 cm, 50 cm, 75 cm, 100 cm, 125 cm, 150 cm, 175 cm, 200 cm). Although there were no statistically significant differences between motor task success in the acquisition or retention period for the practice conditions, self-reported perceptions of target size were impacted by practice condition. During the acquisition period, participants in the self-controlled success and success-late conditions self-reported that the putting hole was larger than did participants in the success-early condition. In the retention period, participants in the self-controlled success condition perceived the target as larger than those in the success-early condition. These findings are the first to show that practice condition, independent of task success, differentially impacted self-reported perception of a target size.